2016
DOI: 10.1016/j.ijid.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial drug use in primary healthcare clinics: a retrospective evaluation

Abstract: This study reports the antibiotic usage at three primary healthcare clinics in Klang Province. The most prescribed antibiotic was amoxicillin in capsules (250mg), which was mainly prescribed for respiratory infections. Although the national antibiotic guidelines state that amoxicillin is a preferred drug for acute bacterial rhinosinusitis, this drug is also being prescribed for other disease conditions, such as acute pharyngitis and acute tonsillitis. This result shows that current practice is not following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 12 publications
(11 reference statements)
8
24
0
1
Order By: Relevance
“…The most used antibiotic agent was amoxicillin, followed by amoxicillin and beta-lactamase inhibitor, levofloxacin, azithromycin, and benzylpenicillin. These results are comparable to those of a study conducted in 48 primary health care facilities sampled from six provinces in China (Wang et al, 2014) and consistent with those from other Asian countries, such as Malaysia and India (Sharma et al, 2012;Shamsuddin et al, 2016). Findings in this study showed a declining antibiotic use.…”
Section: Discussionsupporting
confidence: 90%
“…The most used antibiotic agent was amoxicillin, followed by amoxicillin and beta-lactamase inhibitor, levofloxacin, azithromycin, and benzylpenicillin. These results are comparable to those of a study conducted in 48 primary health care facilities sampled from six provinces in China (Wang et al, 2014) and consistent with those from other Asian countries, such as Malaysia and India (Sharma et al, 2012;Shamsuddin et al, 2016). Findings in this study showed a declining antibiotic use.…”
Section: Discussionsupporting
confidence: 90%
“…The results of our study report a 90.25% of inappropriate prescription in the Health Center that we evaluated. An estimated average of antibiotic prescription appropriateness from studies around the world, mostly including high – middle income countries, is of about 50% [ 8 , 26 31 ]. A review of 344 studies between 1990 and 2009 on the treatment of childhood infections in 78 low-middle income countries reported that a high percentage of viral upper respiratory tract infection cases were being treated with antibiotics, with this percentage increasing over time (from 42% before 1990 up to 72% in 2006–2009) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the care provided in these establishments demands the integration of mental and physical care, that is, the user needs treatment for the disorder, but should also have his/her other needs met, such as an infection, so that resolute and holistic assistance is provided. (22) In terms of costs, pharmaceutical costs with antibiotics for primary care are high, a finding that is supported by other studies in Malaysia (23) and in the United States of America. (24) According to data from the Integrated System of General Services Administration (SIASG), from 2006 to 2013 there was a significant increase in pharmaceutical expenditures by the Brazilian government, with total expenditure tripled (2.72 times), while the amounts purchased only doubled (1.99) during the same period.…”
Section: Discussionmentioning
confidence: 69%